Vibration and low-frequency impact sound generated by normal human walking in lightweight wood-joisted floor-ceiling assemblies - Hu, Lin; Migneron, Jean-Philippe (Canadian Acoustics, 2011)
A study examining vibration and low-frequency impact sound generated by normal human walking in lightweight wood-joisted floor-ceiling assemblies is presented. The sound resembles a pure tone sound at the fundamental natural frequencies of wood floor-ceiling assemblies. The measured sound pressure levels (SPL) of the impact sound using an ISO tapping machine revealed that peak SPL occurred around those frequencies. Due to the limitation of the room height, the thickness of the topping was restricted to around 50 mm. This was another challenge in developing an effective remedy. Direct noise levels in the receiving room wire measured using a tapping machine located in the room above, according to ASTM E1007 method. In order to observe the transmission of the sound through the floor-ceiling assembly at lower frequencies, the spectrum range was extended between 0.8 Hz and 20 kHz. The effect of the topping mass on the impact sound insulation was clearly shown by comparison of third octave spectra measured in the receiving room.